A Relation between Objectivity and Subjectivity in the Moral Reflection of Gabrielė Petkevičaitė during World War I - Barkutė, Skaistė (Respectus Philologicus, 2017)
It is considered that conscience embraces dialectic relation between objectivity and subjectivity. The conviction of an individual conscience is mere subjective conviction so it should satisfy objective moral norms. This article discusses how conscience, as the source of inward responsibility, and objective order of moral rules correlate between each other. Wartime is the limitary situation when the conflict between subjective convictions and objective occasions comes out dramatically clear. In the article it is made attempt to assess how the Lithuanian writer Gabrielė Petkevičaitė authorizes her understanding of right and justice during World War I even if it does not satisfy requirements of objective good. G. Petkevičaitė wrote all reflections of her experience in the diary named Karo meto dienoraštis (The Wartime Diary) in 1914–1919. There is presented Lithuanian writer’s attitude towards prevailing opinion that some of the unwarrantable (sometimes even criminal) actions and behavior are justifiable during such hard limitary times. The texts of the diary reveal the fact that, despite complicated situations, the Lithuanian writer remained true-hearted to humanism ideals and the truth.
Keywords: conscience; objectivity; subjectivity; Gabrielė Petkevičaitė; World War I